2006
DOI: 10.1111/j.1442-2042.2006.01445.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prostate manipulation on the serum levels of complexed prostate‐specific antigen and total prostate‐specific antigen

Abstract: Background:Recently there has been considerable interest in complexed prostate-specific antigen (cPSA) as an alternative to total PSA (tPSA). Data regarding the variations of cPSA are limited. We performed a prospective study using different forms of prostate manipulation to demonstrate and compare variations between cPSA and tPSA. Methods: The study included 113 men, 34 of whom had a digital rectal examination, 28 had a flexible cystoscopy, 17 had a rigid cystoscopy, 21 had a prostate biopsy, and 13 underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…For instance, rise in PSA correlates to the invasiveness of the procedure [61]. Also, PSA levels are detected over a period ranging from few hours to several weeks after treatment [6264]. MLu - PDT causes a short term increase in serum PSA levels, which may be due to cellular damage, leading to release of PSA in circulation [64].…”
Section: Motexafin Lutetiummentioning
confidence: 99%
“…For instance, rise in PSA correlates to the invasiveness of the procedure [61]. Also, PSA levels are detected over a period ranging from few hours to several weeks after treatment [6264]. MLu - PDT causes a short term increase in serum PSA levels, which may be due to cellular damage, leading to release of PSA in circulation [64].…”
Section: Motexafin Lutetiummentioning
confidence: 99%
“…(20-26). The rise in PSA correlates to the invasiveness of procedure (20), and elevated PSA levels are generally detected over a period ranging from less than 1 h to several weeks after the procedure (21-23, 25). The biochemical success of prostate treatment is typically measured through the extent of PSA reduction subsequent to its initial therapy-induced spike (22, 25).…”
Section: Introductionmentioning
confidence: 99%
“…Data from prior studies evaluating PSA change in relation to Table 3 Statistical comparison of total serum PSA levels at 0 and 24 h post CPE cystoscopy have shown variable results, as serum PSA level may either increase or remain the same following cystoscopy. We believe, while it is well accepted, that no urologist may consider an elevated PSA after CPE to be pathological; nevertheless, there is scarcity in published studies evaluating the precise effect of rigid cystoscopy on serum PSA levels, as a recent review of literature suggests that the serum PSA level may increase or remain unaltered following rigid cystoscopy (Table 4) [18,[25][26][27][28][29][30][31][32][33][34]. While the effect of rigid cystoscopy on serum PSA has not been clearly defined in the published literature (Table 4), in our study, we observed a significant rise in the serum PSA levels both at 1 and 24 h following cystoscopy.…”
Section: Discussionmentioning
confidence: 99%